Life of Pi - Lee, Ang; Sharma, Suraj; Khan, Irrfan; Tabu; Spall, Rafe; Depardieu, Gerard; Miranda, Claudio; Twentieth Century Fox Home Entertainment, Inc. (California : Twentieth Century Fox Film, 2012)
After a cataclysmic shipwreck, an Indian boy named Pi finds himself stranded on a lifeboat with a ferocious Bengal tiger. Together, they face nature's majestic grandeur and fury on an epic journey of discovery.
Based upon the novel by Yann Martel.
Executive producer, Dean Geogaris ; director of photography, Claudio Miranda ; film editor, Tim Aquyres ; music by, Mychael Danna.
Cast: Suraj Sharma, Irrfan Khan, Tabu, Rafe Spall, Gerard Depardieu.
DVD format, NTSC, Region 3, Dolby Digital.
In English with optional Malay and Chinese subtitles.
Winner: Academy Awards 2013, Best Directing ; Best Cinematography ; Best Original Score ; Best Visual Effects.
Keywords: Human-animal relationships -- Drama; Shipwreck survival -- Drama; Ocean travel -- Drama